Reactivity of Hexachloroiridate(IV) in Alkaline Medium - Kali Sen Gupta, Kalyan; A.B., Bilkis; Bhattacharjee, Nandini (Asian Journal of Chemistry, 2010)
The reduction of hexachloroiridate(IV) in alkaline medium wasstudied in the temperature range 298-313 K. The reaction is firstorder with respect to [lrCl62-) and [OH-). The rate increases withthe increase in ionic strength. Plot of logarithm of rate constantagainst reciprocal of dielectric constant yields a good straight linewith negative slope up to dielectric constant of ca. 44.4 beyondwhich the line bends. The values of ΔH≠ and ΔS≠ are 59 ± 4 kJmol-1 and -57 ± 14 JK-1 mol-1 respectively. Hexachloroiridate(lV)is reduced to hexachloroiridate(III) by outer sphere mechanisticpath. The reaction appears to proceed through the intermediate formationof free radicals to give products.